Radin Umar is D-G of Higher Education Dept - New Straits Times, (2008)
The Director-General of the Malaysia Institute of Road Safety Research Datuk Prof Dr Radin Umar Radin Sohadi has been appointed Higehr Education Department director-general from Monday.